2023
DOI: 10.3390/ijms24119229
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol-13′-Carboxychromanol Induces Cell Cycle Arrest and Cell Death by Inhibiting the SREBP1-SCD1 Axis and Causing Imbalance in Lipid Desaturation

Abstract: α-Tocopherol-13′-carboxychromanol (α-T-13′-COOH) is an endogenously formed bioactive α-tocopherol metabolite that limits inflammation and has been proposed to exert lipid metabolism-regulatory, pro-apoptotic, and anti-tumoral properties at micromolar concentrations. The mechanisms underlying these cell stress-associated responses are, however, poorly understood. Here, we show that the induction of G0/G1 cell cycle arrest and apoptosis in macrophages triggered by α-T-13′-COOH is associated with the suppressed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…In the present study, cyclin D2 was analyzed and a marginal but insignificant decline in mRNA levels was observed, whereas p21 mRNA levels were not affected. In a recent study, Liao et al 47 demonstrated that α-13′-COOH modulated the cell cycle and insignificantly upregulated p21 gene expression in murine macrophages. Treatment of murine RAW264.7 macrophages with α-13′-COOH resulted in an induction of G0/G1 cell cycle arrest and apoptosis which was associated with a suppressed proteolytic activation of the sterol regulatory element-binding protein (SREBP)1 and with decreased cellular levels of stearoyl-CoA desaturase 1 (SCD1).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cyclin D2 was analyzed and a marginal but insignificant decline in mRNA levels was observed, whereas p21 mRNA levels were not affected. In a recent study, Liao et al 47 demonstrated that α-13′-COOH modulated the cell cycle and insignificantly upregulated p21 gene expression in murine macrophages. Treatment of murine RAW264.7 macrophages with α-13′-COOH resulted in an induction of G0/G1 cell cycle arrest and apoptosis which was associated with a suppressed proteolytic activation of the sterol regulatory element-binding protein (SREBP)1 and with decreased cellular levels of stearoyl-CoA desaturase 1 (SCD1).…”
Section: Discussionmentioning
confidence: 99%